Soluble expression of recombinant cyclophilin A in Escherichia coli - YAN Xiao; XU Li-ren; GUAN Yi-xin; YAO Shan-jing (浙江大学学报. 农业与生命科学版)
To produce a large amount of soluble cyclophilin A (CypA) protein, the recombinant pRSET -CypA plasmid was transferred into E. coli BL21. Using the 2×YT culture medium, the medium compositions of carbon source, nitrogen source and ampicillin concentration were optimized, and the effects of inoculum and induction conditions including inducer concentration, induction time and incubation time were investigated. The results indicated that the recombinant CypA expressed as inclusion bodies was greatly inhibited by controlling the culture temperature and rotating speed of incubator. The mannitol as carbon source could increase the CypA production effectively. The optimized culture medium was composed of peptone 16 g·L-1, yeast extract 10 g·L-1, NaCl 5 g·L-1, mannitol 10 g·L-1, Amp 50 mg·L-1. When OD600 was 1.3, IPTG of 1 mmol·L-1 was added, and the cells were harvested after 9 h cultivation at 30 ℃, 180 r·min-1. After the optimization, the soluble CypA expression reached 66.7 mg·L-1, increased by 76.6% compared with the level under the preoptimized conditions.